2008
DOI: 10.1111/j.1365-2044.2007.05345.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and biochemical effects of balanced salt‐based high molecular weight vs saline‐based low molecular weight hydroxyethyl starch solutions during the anhepatic period of liver transplantation

Abstract: SummaryThe anhepatic period of liver transplantation is generally marked by a decrease in preload, and the infusion of hydroxyethyl starch (HES) solution is often an effective way to restore volume deficits in non-anaemic patients. However, the infusion of even limited amounts of HES solution during the anhepatic period may result in a worsening coagulopathy. Moreover, lactate-containing HES solution may cause some degree of biochemical derangements in compromised recipients. Therefore, we compared two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…When administered in large volumes, 0·9 per cent saline has been shown to cause coagulopathy. Total volumes of fluid administered did not vary substantially between the groups ( Table S3 , supporting information), suggesting that dilutional coagulopathy does not account for the observed differences in transfusion.…”
Section: Discussionmentioning
confidence: 91%
“…When administered in large volumes, 0·9 per cent saline has been shown to cause coagulopathy. Total volumes of fluid administered did not vary substantially between the groups ( Table S3 , supporting information), suggesting that dilutional coagulopathy does not account for the observed differences in transfusion.…”
Section: Discussionmentioning
confidence: 91%
“…We chose this regimen because of two main reasons: first, cirrhotic patients might potentially have some degree of capillary leakage, and a colloid would theoretically remain inside the intravascular space more readily; secondly, we chose a relatively small infusion volume for each FC because of concerns of colloid-induced coagulopathy, as it has been shown that the volume threshold to induce coagulopathy may be unexpectedly low in cirrhotic patients undergoing OLT. 26 Another explanation for our results would be the setting where this study was performed. Accordingly, acute changes in sympathetic tone and preload status might be particularly frequent during major abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between fluid overload and morbidity and mortality were reported by the Fluid and Catheter Treatment Trial (FACTT) and other trials in surgical patients [ 22 24 ]. When administered in large volumes, NS has been shown to cause coagulopathy [ 25 , 26 ]. The mechanisms underlying saline-induced coagulopathy are not fully known.…”
Section: Discussionmentioning
confidence: 99%